Solid-Liquid Equilibrium Study for Binary System Forming Intermolecular Compound: Phase Diagram, Thermal, Physicochemical and Powder XRD study - Sharma, Krishna; Ghimire, Prakash; Neupane, Umesh (Journal of Nepal Chemical Society, 2022)
The phase diagram study of the binary organic system has been investigated by the thaw melt method using 4-hydroxy- 3 methoxybenzaldehyde (HMB) and 4-nitroaniline (NA). The temperature-composition plot showed that the intermolecular compound (IMC) has formed at 1:1 molar ratio with two eutectics on either side of IMC. The melting points of eutectics and IMC along with parents are verified by the DSC method. The different phases of the systems which are in equilibrium and their physicochemical properties are estimated using the enthalpy of fusion values obtained from DSC. The higher melting temperature of IMC suggested the formation of Schiff base during homogenization process. The new and moderately sharp Bragg’s peaks at specific 2θ values found in the diffractogram of IMC revealed the novelty and crystalline nature of IMC while repeated peaks in the diffractogram of eutectics suggest the mechanical mixture of eutectics